O desastre no Rio Doce sob a ótica da governança e das capacidades estatais no nível municipal: os casos de Linhares e Colatina - Silva, Paolo de Souza (2023)
This study analyzes the construction of state capacities and the legacy of environmental governance in two municipalities affected by the aftermath of the rupture of the Fundão and Santarém dams, belonging to the mining company Samarco and located in the district of Bento Rodrigues, municipality of Mariana, Minas Gerais, impacting the environment and living conditions of the population in a large part of the Rio Doce Basin. Empirically, we compare patterns of institutionalization and construction of administrative and political capacities related to the production of environmental public policies, in the Espírito Santo municipalities of Colatina and Linhares. The study articulates the concepts of political science, especially those in the area of public policies, such as state capabilities and governance to present the institutional arrangement of environmental policies, as well as to analyze the technical and political relational capabilities through sixteen categories formulated from the specificities of the cases studied. In this way, we seek to contribute to the consolidation and articulation of the dialogue between the literatures through a review of the concepts and their applicability. The results showed differences in the patterns of response and institutionalization, as well as differences in the levels of articulation between actors in the institutional arrangement, structures and available resources.